Reisetexte der russischen Moderne Andrej Belyj und Osip Mandel'štam im Kaukasus - Sippl, Carmen (Slavistische Beitraege, 1997)
Two outstanding representatives of Russian modernism - Andrei Belyy for the movement of symbolism, Osip Mandel'tam for acmeism - chose the Caucasus as a tourist destination for their travels in the last decade of their lives within the borders of the Soviet Union. For both, the cultural-historical context was crucial in several ways in this choice. It concerns, on the one hand, the poet's own person and his cultural awareness, which refers to his integration into traditional contexts both in Russian and in world culture. On the other hand, Belyj and Mandel'štam in the Caucasus are looking for an encounter with a cultural space which, through its rich history, during which it has been exposed to a variety of foreign influences and yet retains its specific character, is able to provide these two factors in a unique way ,